Adapting Grapevine Productivity and Fitness to Water Deficit by Means of Naturalized Rootstocks - Villalobos-Soublett, Emilio; Verdugo-Vásquez, Nicolás; Díaz, Irina; Zurita-Silva, Andrés (Frontiers in Plant Science, 2022)
The climate change effects are unbalanced in all regions and cultivars linked to the wine industry. However, the impact of extreme weather events such as drought and rising global temperatures highlight the potential vulnerability in plant productivity, phenology and crop water requirements that affects quality and harvests. Among adaptative measures for grapevine cultivars in existing or new winegrowing areas, the use of tolerant rootstocks to abiotic stress has been regarded as mid-term strategy to face emerging constrains. The aim of this study was to compare naturalized or autochthonous rootstocks influence over grapevine cultivars performance and to characterize their response to deficit irrigation conditions. Data was collected from Cabernet Sauvignon and Syrah grafted plants over 3 growing seasons (2018–2021) from a hyper-arid experimental field in Vicuña, Chile. Morpho-physiological parameters were determined throughout seasons and combinations, where significant effects from rootstocks, irrigation treatment and cultivar were observed over An and gs thus modifying CO2 assimilation and WUEi. Primary productivity and yield were also modified by rootstock depending upon cultivar hydric behavior. Interestingly, cluster and berry traits were unaffected despite that water productivity and integral water stress were modulated by rootstock. In both cultivars it was observed that trait responses varied according to the irrigation conditions, rootstocks, and their respective interactions, thus highlighting a relative influence of the rootstocks in the processes of adaptation to the water deficit. Moreover, harvest date and acidity were modified by deficit irrigation treatment and rootstocks did not modify phenological stages. Adaptation of grapevines to expected lower water availability might be improved by using suitable tolerant rootstocks and maturity index can be modified through irrigation management.